Age-Related Effects of Varying Ammonia Concentrations on Hematophysiological Variables in Broiler Chickens - Olanrewaju, H.A.; Purswell, J.L.; Collier, S.D.; Branton, S.L. (International Journal of Poultry Science, 2009)
This study examined the response of different aged birds of the same genetic strain exposed to ammonia (NH3) at set concentrations on blood gases, electrolytes and acid-base balance under environmentally controlled conditions. The experiment consisted of a 4x4 factorial with a randomized design. The 16 treatments consisted of 4 levels (0, 25, 50 and 75 ppm) of NH3 concentrations and 4 different ages (1-d, 7-d, 14-d and 21-d) of birds. Venous blood samples were collected at the end of each 7 d of atmospheric NH3 exposure. Partial pressure of CO2 (pCO2), pH, Hematocrit (Hct) and Hemoglobin (Hb) increased significantly (p